NEW TECHNOLOGIES AS A FACTOR CHANGING THE INDUSTRY (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2024)
In the article, the author discusses the obstacles faced by industrial enterprises in Uzbekistan in the development of technology transfer. He emphasizes the importance of state support, education and cooperation between universities and business. The article is intended for experts in the field of innovation, economics and management, as well as for government agencies seeking to improve conditions for successful technology transfer.